Outcome of micro-lumbar discectomy and preventive measures to control discitis (Nepal Journal of Neuroscience, 2020)
Objective: The purpose of the present study is to describe the rate of post-operative discitis following micro-lumbar discectomy.Methods and Materials: This is a retrospective study of 203 patients who underwent micro-lumbar discectomy between March 2015 and April 2018 in our institute. Prior to surgery, patients were optimized by maintaining personal hygiene, controlling blood sugar in diabetics and withholding steroids. Standardized intra-operative measures were taken to prevent discitis. Post-operatively on day 7, patients were evaluated for symptoms like back pain, fever and wound infection. If there was any sign of infection then the patient was evaluated with a plain x-ray of lumbosacral spine, inflammatory blood markers like complete blood count, erythrocyte sedimentation rate, C-reactive protein and Magnetic Resonance Imaging of lumbosacral spine to rule out discitis.Results: There were 127 males and 76 females, the age ranging from 8 years to 80 years. MRI imaging showed 94.6% single and 5.4% multilevel disc prolapses with 4.2% high lumbar and 95.8% low lumbar disc prolapse. Indications for surgery were failed conservative treatment (44), intractable pain (102), neurological deficit (49), and cauda equina syndrome (8). None of the 203 patients developed post-operative discitis, however, some of them had nerve root injury (4), dural tear (5), wound infection (5) and pseudo-meningocele (2). Almost all patients were mobilized within 48 hours (98%) after surgery. 95% were discharged on the 7th day of surgery and 5% within two weeks. Radicular pain was relieved in 92% patients within one week, 6% within three weeks and 2% had no change. Low back pain was relieved in 80% of patients in three weeks, 15% in three months and 5% had persistent back pain. The recurrence rate was 2.5% in our series. 80% had joined their previous job after four weeks, 15% after three months and 5% had changed their job.Conclusions: Post-operative discitis can be prevented if appropriate precautions are taken like using separate dedicated neurosurgical operation theatre, prophylactic antibiotics, minimally invasive procedure and not curating the end-plates.